KOHA ILS: The Next Level - Abu Bakar, Amzari; Rahmad, Fadhilnor; Mohd Amin, Zahari (2015)
Koha is an Open Source Integrated Library Systems was developed in 1999. Koha has been adopted by libraries in Malaysia starting in 2008. After 7 years, Koha has been chosen by significant numbers of libraries in Malaysia including large academic library recently. The trend gives indication of library acceptance in Open Source Software as compared to other Open Source ILS Software. This paper intends to discuss post implementation of Koha Open Source ILS in perspectives; technical perspective, new suggested features and managerial perspective related to Koha and open source software. This paper gives overview of selected features that might be missed by Koha users, what more can be done with the system and few critical issues in managing open source software implementation.